2008
DOI: 10.1203/pdr.0b013e31815b8e60
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Isoflavones on Proliferation and DNA Integrity of Myoblasts Derived from Newborn Piglets

Abstract: Soy-based formulas are consumed by growing numbers of infants and used as regular food supplements in livestock production. Moreover, constituent dietary phytoestrogens may compete with endogenous estrogens and affect individual growth. This study aimed to investigate the in vitro effects of isoflavones in comparison with estrogens on the proliferation of porcine satellite cells derived from neonatal muscle. After 7 h of exposure in serumfree medium, 17␤-estradiol (1 nM, 1 M), estrone (1 M), and daidzein (1, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Our findings support the potential of ISF as an intestinal protective agent in young piglets with its attenuation of intestinal damage induced by oxidative stress. Although several studies have evaluated the effectiveness of ISF on piglets (de Wilde et al, 2004;Mau et al, 2008;Goerke et al, 2012), none of these studies examined the effectiveness of ISF treatment on the oxidative stress and immune function of the piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the potential of ISF as an intestinal protective agent in young piglets with its attenuation of intestinal damage induced by oxidative stress. Although several studies have evaluated the effectiveness of ISF on piglets (de Wilde et al, 2004;Mau et al, 2008;Goerke et al, 2012), none of these studies examined the effectiveness of ISF treatment on the oxidative stress and immune function of the piglets.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferating and differentiating cultures grown under the described conditions are eminently suitable to study the effects of various bioactive compounds like nutrients, hormones, and growth factors, e.g., the influence of isoflavones, IGF-I, or EGF (Mau et al , 2008. Alternatively, the culture conditions could be optionally modified using 1-5% FBS for differentiation (e.g., Ortenblad et al 2003) in the case that serum-free conditions are not necessary.…”
mentioning
confidence: 99%
“…However, a number of other hormones, growth factors (e.g. myostatin) and nutrients have also been shown to regulate myoblast proliferation and differentiation directly and therefore are also likely to play a role (see reviews by Maltin et al, 2001;Picard et al, 2002;Brameld et al, 2003;Brameld and Daniel, 2008) including antioxidants , soyaderived isoflavones (Mau et al, 2008a) and unsaturated fatty acids (Hurley et al, 2006; see also 'Environmental impact on skeletal muscle development and consequences for animal growth, carcass and meat quality').…”
Section: Critical Timings and Mechanismsmentioning
confidence: 99%
“…The in vitro studies on the direct effects of isoflavones on muscle cells may be a model for the effects of maternal diet on muscle development. Results revealed that genistein and daidzein act as inhibitors of porcine myoblast proliferation at concentrations of .1 and .10 mM, respectively (Mau et al, 2008a), and that they interact with growth factor (IGF-I; EGF)-stimulated porcine muscle cell proliferation (Mau et al, 2008b;Kalbe et al, 2008). Reduced proliferation, in part, resulted from the inhibition of the expression of these growth factors and their receptors.…”
Section: Consequences Of Maternal Nutritionmentioning
confidence: 99%